Computational modelling of aerodynamic disturbances on spacecraft within a concurrent engineering framework - Graziano, Benjamin P. (Cranfield University, 2007)
This research was motivated by the need to perform an accurate aerodynamic analysis of the drag deorbit device concept under development within the Space Research Centre, Cranfield University. Its purpose is to deorbit satellites from low Earth orbit at the end of the useful lives, in order to help reduce the growing problem of space debris. It has been found that existing spacecraft aerodynamic analysis tools do not adequately support concurrent engineering. Furthermore, use of concurrent engineering in the space industry is currently limited to Phase A (preliminary design studies). To remedy this, the Spacecraft Engineering, Design, and Analysis Tools (SEDAT) Concept has been proposed. Inspired by the approach employed by enterprise applications, it proposes that all the computer tools used on a spacecraft project should be incorporated into one system as separate modules, presented via a single client, and connected to a centralised Relational Database Management System. To demonstrate the concept and assess its potential a SEDAT System and accompanying Free Molecular Flow (FMF) spacecraft aerodynamic analysis module have been developed. The FMF Module is explicitly designed to facilitate concurrent engineering and make use of the maximum variety of Gas-Surface Interaction Models (GSIMs) and their associated data. It also incorporates a new Hybrid method of FMF analysis that combines the Ray-Tracing Panel (RTP) and Test-Particle Monte Carlo (TPMC) methods, enabling it to analyse complex geometries that are subject to surface shielding and multiple molecular reflections. Studies have been performed using a Hybrid version of the Schaaf and Chambre GSIM. One of these studies analysed a drag deorbit device design using a range of accommodation coefficients, including the latest empirically based incidence-dependent coefficients. Based on this analysis, recommendations have been made regarding the material selection and structural design of the device.